UMKM GO DIGITAL: STRATEGI MEMPERLUAS PASAR DI ERA ONLINE - Nurul Aisyah Rachmawati; Rizka Ramayanti; Erneza Dewi Krishnasari; Athallah Akmal; Dwi Maharani Putri; Ersya Pramestina Meilani; Anugrah Dafa Satria (Jurnal Pepadu, 2025)
One of the classic problems often faced by Micro, Small, and Medium Enterprises (MSMEs) is low digital marketing literacy. A similar issue was also experienced by the MSME group fostered by the Jatibening Family Income Improvement Business (UP2K). Without this literacy, MSMEs struggle to develop effective and targeted marketing strategies. The community service team will provide training and mentoring to MSME partners regarding digital marketing strategies as a solution to the existing problem. This community service program is funded by the Directorate of Research and Community Service (DPPM) of the Ministry of Higher Education, Science, and Technology (KemdiktiSaintek) of the Republic of Indonesia through the BIMA Grant for the Community Partnership Empowerment scheme for the 2025 funding year. MSME partners were very enthusiastic in participating in the activity. It is hoped that with the right digital marketing strategy, MSME partners can reach a wider market, be more efficient in promotional costs, increase sales, understand consumer behavior, and clearly measure promotional results.